Cloud Computing: Principles, Systems and Applications - Antonopoulos, Nick; Gillam, Lee (Computer Communications and Networks, 2010)
This essential reference is a thorough and timely examination of the services, interfaces and types of applications that can be executed on cloud-based systems. Among other things, it identifies and highlights state-of-the-art techniques and methodologies.